KONTRIBUSI PEMANFAATAN FASILITAS WIFI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KOMPUTER DAN JARINGAN DASAR - Rosfina Rosfina; Nelda Azhar (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study examines the use of wifi facilities and learning motivation towards student learning outcomes by using descriptive correlational research methods carried out with a quantitative approach. In order to find out the value below the graduation standard for the total population of 40 students in the study carried out using a quitionnaire technique which later the data used was collected through a questionnaire (quistionnaire) so that the primary data obtained in the form of student grades. After that, the data was tested with descriptive assessment techniques and normality and linearity tests which aimed to prove the delivery of data taken from samples that had been allocated normally, linear homogeneous, multicollinearity and decision making. Based on the results of the study there is a relevant correlation between variables X1 and X2 which get 40.6% and 14.3% of the Y variable with a result of 33.5%. Keywords:Use of WiFi Facilities, Learning Motivation and Learning Outcom